A judicialização das internações compulsórias na saúde mental: gestão e intersetoridade - Adriano Neves Coelho (2021)
The study sought to identify the cases of judicialization of compulsory hospitalizations of mental health in the municipality of Betim, Minas Gerais, in the period from 2017 to 2019, in order to establish a flow of intersectoral actions between the trial court and the Municipal Health Secretariat / Social Assistance department, thus optimizing the allocation of financial resources now employed in compliance with court decisions. We opted for a qualitative approach, of documentary research, based on primary data contained in public databases and norms of the Municipality of Betim. It was observed that the judicialization of the treatment of patients with metal disorder is due to the lack of investment in this type of treatment in the city, since what could be less expensive for the city becomes an amount to be paid by the city unexpectedly and at any time, due to the possibility of a new judicialization to pay for the treatment of another patient in the city. We conclude that the psychiatric disorder, although it has been studied all over the country, needs to be further studied in order to ease the suffering of patients and their families. The non-assistance of these patients was observed, thus causing the families to seek treatment for their loved ones in court, which could be avoided if there were the necessary investment by the city government in question.